The Use of Chemsketch To Increase Student Learning Outcomes and Motivation In Learning Hydrocarbons - Jesi Jecsen Pongkendek; Dewi Natalia Marpaung; Evi Nurvitasari; John Yoro Parlindungan (Universitas Negeri Malang, 2021)
Learning motivation is an encouragement in students to be able to learn well, add skills and provide learning experiences. High learning motivation will improve learning outcomes. This research is quantitative research to determine students' learning motivation, student learning outcomes, and the relationship between learning motivation and learning outcomes in learning chemistry on Hydrocarbon material with the application of Chemsketch media. The research was conducted at SMAN 2 Merauke in Class XI IPA 1 with 28 students. The sampling technique used is simple random sampling. The research data was obtained by using learning outcomes tests and learning motivation questionnaires. The research data were analyzed descriptively and the results obtained were: (1) student learning outcomes with an average score of 81,86 with 25 students passed the test and 3 students not past the test, (2) students' learning motivation with an average score of 80, 86 with 11 people in the very high category and 17 people in the high category. Followed by quantitative data analysis to test the linearity of the data, the normality of the data, and the correlation between learning motivation and learning outcomes with the Pearson bivariate correlation test. After analyzing the results obtained that (1) there is a linear and significant relationship, (2) the data is normally distributed, (3) there is a significant relationship between learning motivation and learning outcomes.ReferencesAbidin, Z., & Ijrah, S. (2018). Hubungan Motivasi Belajar dengan Hasil Belajar Pada Siswa Kelas V SD Negeri Gugus IV Kecamatan Banuhamou Kabupaten Agam. Jurnal Inovasi Pendidikan dan Pembelajaran Sekolah Dasar, 2(2), 21–29.Azrai, E. P., Ernawati, E., & Sulistianingrum, G. (2017). Pengaruh Gaya Belajar David Kolb (Diverger, Assimilator, Converger, Accommodator) Terhadap Hasil Belajar Siswa Pada Materi Pencemaran Lingkungan. Biosfer: Jurnal Pendidikan Biologi, 10(1), 9–16. https://doi.org/10.21009/biosferjpb.10-1.2Betaubun, M., Asmaningrum, H. P., & Nasrawati. (2020). Analisis Kebutuhan E-book Interaktif Bilingual Etnokimia dengan Pendekatan Konstruktivisme. Magistra, 7(1), 10–22.Farid, A., & Nurhayati, S. (2014). Pengaruh Penerapan Strategi React Terhadap Hasil Belajar Kimia Siswa Kelas XI. Chemistry in Education, 3(1).Hamalik, O. (2001). Teknik Pengukuran dan Evaluasi Pendidikan. CV. Mandar Maju.Handhika, J. (2012). Efektivitas Media Pembelajaran IM3 Ditinjau dari Motivasi Belajar. Jurnal Pendidikan IPA Indonesia, 1(2), 109–114. https://doi.org/10.15294/jpii.v1i2.2127Harahap, S. N., & Siregar, M. F. (2019). Pengaruh Model Pembelajaran Dengan Mengintegrasikan Strategi Pembelajaran Cooperative Learning Tipe STAD Dengan Media Chemsketch Terhadap Hasil Belajar Siswa. Cyberspace : Jurnal Pendidikan Teknologi Informasi, 3(1), 1–7. https://doi.org/10.1017/CBO9781107415324.004Harta, J., Limbong, S. A., & Waruwu, E. E. (2020). Pengembangan Media Pembelajaran Asam Basa Inovatif Berbasis Green Labyrinth untuk SMA. J-PEK (Jurnal Pembelajaran Kimia), 5(1), 17–31. https://doi.org/10.17977/um026v5i12020p017Indriyanti, N. Y., Widisatuti, A., Suryadi, B. U., & Hasanah, N. (2020). Pemberdayaan Guru Kimia Melalui Produksi Media Pembelajaran Berbasis Aplikasi Chemsketch. Jurnal Bakti Saintek, 4(1), 23–26. https://doi.org/10.14421/jbs.1566Iqbal, M., & Tarigan, I. L. (2019). Pengaruh Model Pembelajaran Siklus Belajar 5E Menggunakan Media Animasi Terhadap Aktivitas Belajar Dan Hasil Belajar Siswa SMA Kelas XI Pada Materi Hidrolisis Garam. J-PEK (Jurnal Pembelajaran Kimia), 4(1), 31–38. https://doi.org/10.17977/um026v4i12019p031Linda, R., Herdini, & Rahmaputri, Z. (2017). Multimedia interaktif berbasis autoplay media studio 8 untuk mata pelajaran kimia pokok bahasan laju reaksi untuk kelas XI SMA/MA. Jurnal Pendidikan Kimia, 9(3), 347–351.Lumentut, R. S., Said, I., & Mustapa, K. (2017). Pengaruh Model Pembelajaran Guided Inquiry dengan Mind Map terhadap Hasil Belajar dan Motivasi Siswa pada Materi Redoks di Kelas X SMA Negeri 5 Palu. Jurnal Akademika Kimia, 6(2), 113–118. https://doi.org/10.22487/j24775185.2017.v6.i2.9242Marpaung, D. N., Siregar, L. F., & Pongkendek, J. J. (2019). The development of innovative learning material integrated with environmental activities to improve student learning outcomes on electrolyte and nonelectrolyte solution. IOP Conference Series: Earth and Environmental Science, 343(1). https://doi.org/10.1088/1755-1315/343/1/012218Marpaung, Dewi Natalia. (2019). Implementation of Active and Creative Learning Through Multimedia on the Teaching of Solubility and Solubility Product. Journal of Basic and Applied Scientific Research, 9(6), 42–46.Mbosisi, S. B., & Mustapa, K. (2018). Pengaruh Penerapan Model Pembelajaran Kooperatif Tipe Teams Games Tournament Berbasis Scramble Terhadap Motivasi dan Hasil Belajar Siswa SMA Kristen GPID Palu. Jurnal Akademika Kimia, 7(1), 36–40.Mediawati, E. (2010). Pengaruh Motivasi Belajar Mahasiswa Dan Kompetensi Dosen Terhadap Prestasi Belajar. Dinamika Pendidikan, 5(2), 134–146. https://doi.org/10.15294/dp.v5i2.4922Nazalin, N., & Muhtadi, A. (2016). Pengembangan Multimedia Interaktif Pembelajaran Kimia Pada Materi Hidrokarbon Untuk Siswa Kelas XI SMA. Jurnal Inovasi Teknologi Pendidikan, 3(2), 221. https://doi.org/10.21831/jitp.v3i2.7359Novita Yanda, S., & Safitri, Y. (2018). The Effect of Using E-learning Material on Hydrocarbon Chapter to Improve Students’ Achievement Motivation in Learning Chemistry. ICESST 2018, 843–847. https://doi.org/10.29210/20181122Palittin, I. D., Wolo, W., & Purwanty, R. (2019). Hubungan Motivasi Belajar dengan Hasil Belajar Siswa. Magistra, 6(2), 110–118.Pongkendek, J. J., Parlindungan, J. Y., & Marpaung, D. N. (2019). Effectiveness of the Application of Team Games Tournament Cooperative Learning Model (TGT) to Improve Learning Outcomes of Students of Class XI Science 1 SMA Frater Makassar in the Principal Material of Salt Hydrolysis. IOP Conference Series: Earth and Environmental Science, 343(1). https://doi.org/10.1088/1755-1315/343/1/012228Pongkendek, Jesi Jecsen, Marpaung, D. N., & Siregar, L. F. (2019). Analisis Motivasi Belajar Siswa Dengan Penerapan Model Pembelajaran Kooperatif Tipe Team Games Tournament. Musamus Journal of Science Education, 2(1), 31–38. https://doi.org/10.35724/mjose.v2i1.2243Raiyn, J., & Rayan, A. (2015). How Chemicals ’ Drawing and Modeling Improve Chemistry Teaching in Colleges of Education. World Journal of Chemical Education, 3(1), 1–4. https://doi.org/10.12691/wjce-3-1-1Sardiman. (2011). Interaksi dan Motivasi Belajar Mengajar. PT. Raja Grafindo.Septryanesti, N., & Lazulva, L. (2019). Desain Dan Uji Coba E-Modul Pembelajaran Kimia Berbasis Blog Pada Materi Hidrokarbon. JTK (Jurnal Tadris Kimiya), 4(2), 202–215. https://doi.org/10.15575/jtk.v4i2.5659Sitepu, C. P. K. (2016). Pengaruh Pemanfaatan Media Chemsketch Dalam Pembelajaran Yang Menggunakan Metode Resitasi Terhadap Motivasi Dan Hasil Belajar Kimia Di SMK Kelas XI. Jurnal Ilmiah “INTEGRITAS,” 2(1).Sitepu, C., & Simanjuntak, R. (2018). Upaya Meningkatkan Hasil Belajar Mahasiswa Pada Materi Bentuk Molekul Dengan Model Pembelajaran Kooperatif Tipe Think Pair Share (TPS) Berbantuan Media Physics Education Technology (PhET) Dan Chemsketch. JURNAL Suluh Pendidikan FKIP-UHN, 5(2), 36–47. https://doi.org/10.1017/CBO9781107415324.004Utami, H. H., Sulfikar, & Anwar, M. (2017). Pengaruh Chemsketch Dalam Penulisan Struktur Kimia Pada Merode Resitasi Terhadap Hasil Belajar Siswa (Materi Pokok Ikatan Kimia). Jurnal Penelitian Pendidikan INSANI, Vol.20(No.2), 96–100.Yuliany, N. (2018). Relationship Between Learning Motivation to Learning Result Mathematics Students. AULADUNA, 5(2), 126–137.